Role of Parents and Teachers in the Social Development of Students (Journal of Social Sciences Review, 2023)
This research paper has been carried out to explore the role of teachers and parents in the social development of children and transforming them into potential beings of society with technological support. A technique called "judgmental sampling" or "intentional sampling" was used to choose the sample size of 130 people. The people who took part were the kids' birth parents. A questionnaire was made beforehand to collect information, and the chi-square test was used to determine what it all meant. This study shows how important it is for special educators, trainers, teachers, and psychologists to help children develop academically and socially to become valuable members of society. The training and development of children in a city should use cutting-edge technology and new ways of looking at education to help them grow and succeed in society. Schools are encouraged to give special education teachers seminars, workshops, and courses yearly to help them improve their professional skills. Seminars on awareness and Counseling for parents are also on the list of things that should be required. Parents, teachers, and the general public all need to know more about the problems children face today.
Keywords: Teachers; Parents; Social Development; Students; Society